Combined malonic and methylmalonic aciduria: exome sequencing reveals mutations in the ACSF3 gene in patients with a non-classic phenotype. Issue 9 (23rd July 2011) - Alfares, Ahmed; Nunez, Laura Dempsey; Al-Thihli, Khalid; Mitchell, John; Melançon, Serge; Anastasio, Natascia; Ha, Kevin C H; Majewski, Jacek; Rosenblatt, David S; Braverman, Nancy
Abstract : Background: Combined Malonic and Methylmalonic Aciduria (CMAMMA) is a rare recessive inborn error of metabolism characterised by elevations of urine malonic acid (MA) and methylmalonic acid (MMA). Nearly all reported cases are caused by malonyl-CoA decarboxylase (MCD) deficiency. Most patients have metabolic acidosis, developmental delay, seizures and cardiomyopathy. CMAMMA was also described in symptomatic patients with normal MCD activity, suggesting heterogeneity in this disorder. Methods and results: We identified two probands with a non-classical CMAMMA variant through the Quebec newborn urine screening program. While they share the biochemical phenotype of elevated MA and MMA, the MMA excretion was higher than MA, the clinical courses were benign, MYLCD gene sequencing was normal and MCD activity, measured in one proband, was normal. Using exome sequencing in the single consanguineous proband, we identified a homozygous missense allele in the ACSF3 gene, encoding an Acyl-CoA Synthetase (ACS) with unknown substrate and function. The second proband was homozygous for a different ACSF3 missense allele. Both substitutions were in conserved residues and were identified in less than 0.5% of their respective ethnic control populations. Conclusion: These results suggest that ACSF3 is a candidate gene for non-classical CMAMMA observed in our patients and document the value of exome sequencing of a limited number of patients for the identification of novel disease genes.